Understanding Recreational Fishers Disciplinary and Interdisciplinary Approaches for Fisheries Management - Pope, Kevin L.; Arlinghaus, Robert; Hunt, Len M.; Lynch, Abigail J.; van Poorten, Brett T.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2026)
This open access book unites experts from a range of social-science disciplines. It provides a multidisciplinary and interdisciplinary overview of how to study recreational fishers as coupled social-ecological system, presenting unique methodological insights for an improved understanding and management of recreational fisheries. The book informs readers about state-of-the art methods for engaging fishers, for quantifying and predicting fisher behaviors, for understanding outcomes of fisher behaviors, and for fully integrating social-science data into recreational-fisheries management$1 (Ball in the hopes to support sustainable management of complex social-ecological fisheries systems. The content appeals to social scientists and ecologists alike. It is a key resource for students, fisheries managers and fisheries biologists, especially those without formal training in social sciences, and for research scientists and educators developing programs and courses in the field of human dimensions of fish and wildlife. While focused on recreational fisheries, the toolsets and integrative concepts summarized in this book will be of interest to many other natural resource and biodiversity management contexts where humans and the environment interact.s
Part I. Recreational Fisheries -- Chapter 1. Complexity and Integration of Recreational Fisheries -- Chapter 2. Role of Recreational Fisher Information in Fisheries Management -- Part II. Disciplinary Views of Fishers$1 (BBehaviours and Outcomes -- Chapter 3. Introducing Disciplinary Perspectives and Interdisciplinary Possibilities for Understanding Recreational Fishers and Fisheries -- Chapter 4. Ecology for Understanding Recreational Fishers and Fisheries -- Chapter 5. Resource Economics for Understanding Recreational Fishers and Fisheries -- Chapter 6. Social Psychology for Understanding Recreational Fishers and Fisheries -- Chapter 7. Political Ecology for Understanding Recreational Fishers and Fisheries -- Chapter 8. Environmental History and Historical Ecology for Understanding Recreational Fishers and Fisheries -- Chapter 9. Behavioural Economics for Understanding Recreational Fishers and Fisheries -- Part III. Engaging Fishers to Support Effective Social Science -- Chapter 10. Guidelines for Writing and Constructing Recreational Fisher Surveys -- Chapter 11. Fundamentals of Sampling and Implementing Human Dimensions of Fishing Surveys -- Chapter 12. Measurement Instruments -- Chapter 13. Optimizing Creel Surveys -- Chapter 14. Economic Experiments in Recreational Fishing Studies -- Chapter 15. Digital Data Mining -- Chapter 16. Mixed Methods Research: Applications and Considerations for the Human Dimensions of Recreational Fisheries -- Chapter 17. Quantitative and Qualitative Content Analysis of Text and Images -- Chapter 18. Knowledge Co-production in Recreational Fisheries Science and Management -- Chapter 19. Evidence Synthesis in Recreational Fisheries Science and Management -- Part IV. Interdisciplinary Integration for Recreational Fisheries Management -- Chapter 20. Integrating Diverse Stakeholder Knowledge in Recreational Fisheries Decision Making -- Chapter 21. Integrated Models of the Social-ecological Dynamics of Recreational Fisheries -- Chapter 22. Participatory Modelling to Support Evaluation of Management Actions for Recreational Fisheries -- Chapter 23. Adaptive Management for Recreational Fisheries Decisions in the Face of Uncertainty -- Chapter 24. Data Standardisation and Management to Facilitate Large-scale and Interdisciplinary Approaches -- Chapter 25. Best Practices for Understanding Recreational Fishers.s
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Freshwater ecology; Marine ecology; Biology -- Technique; Science -- Social aspects; Freshwater and Marine Ecology; Behavioral Methods; Sociology of Science